Developing English Rubric for Describing the Student’s Basic Language Skill Competence in Student’s Report Card - Metekohy, Johannes (Widya Mandala Surabaya Catholic University, 2021)
As a subject of learning, English also needs to be considered for its aspects. One of them is the assessment. Assessment of English should cover all language skills. The content to be taught involves this implicitly. A more detailed and uniqueness of the scores given to each student should reflect the student’s achievement in a certain cycle of learning. However, the way of reporting a student’s achievement doesn’t really imply all of the aspects. It is only reported as a single score with a very limited description verbally. This research, through its methodology, gathers some data related to the lack of student’s score description, starting from the parents’ questions about it until some experts’ comments on it. The answer is about reporting student’s achievement in the form that involves the aspects of teaching learning English in the classroom using a certain tool. This tool is made using some parameters including the basic competence, indicator of it, score range and the rubric. The final result is a complete description of student’s score for each cycle of language skill and description about the scores. This way, it is expected stake holder and the student can have a complete explanation of their assessment distinctively.